x2 − 12x + 27?
Answer:
The factors of the expression in the question x² − 12x + 27 = 0 are (x - 9)(x -3) .
Step-by-step explanation:
As given the expression in the question be as follow .
x² − 12x + 27 = 0
x² - 9x - 3x + 27 = 0
x (x - 9) -3 (x -9) = 0
(x - 9)(x -3) = 0
Therefore the factors of the expression in the question x² − 12x + 27 = 0 are (x - 9)(x -3) .
The factored form of the polynomial ( x² - 12x + 27 ) is ( x-3 )( x-9 ).
Given that;
First, we think of two numbers where their addition gives -12 and their multiplication gives 27.
-3 and -9 fits perfectly.
Hence we have;
x² - 12x + 27
( x-3 )( x-9 )
Therefore, the factored form of the polynomial ( x² - 12x + 27 ) is ( x-3 )( x-9 ).
Learn more about factorizations here: brainly.com/question/1863222
#SPJ5
Josephine will receive approximately 70 advertisements in the next 100 e-mails she receives.
The possibility of an event in time is known as probability in mathematics. How frequently does the incidence occur over the course of a specific time period, in plain English?
If Josephine received 7 advertisements out of 10 e-mails, then we can say that the probability of receiving an advertisement in a single e-mail is 7/10 or 0.7.
Assuming that the probability of receiving an advertisement in an e-mail remains the same for all e-mails, we can use this probability to make a prediction about the number of advertisements she will receive in the next 100 e-mails.
The expected number of advertisements in 100 e-mails can be calculated by multiplying the probability of receiving an advertisement in a single e-mail by the total number of e-mails:
Expected number of advertisements = probability of an advertisement x total number of e-mails
= 0.7 x 100
= 70
Therefore, based on the given information, we can predict that Josephine will receive approximately 70 advertisements in the next 100 e-mails she receives.
To learn more about the probability;
#SPJ3
Answer:
Step-by-step explanation:
Let α be one of the zeros of the polynomial.
Other = 4α
α + 4α = - Coefficient of x / Coefficient of x² = -5/3
5α = -5/3
α = -5/3*5
α = -1/3
α * 4α = Constant term/Coefficient of x²
4α² = k / 3